REVIEW ON FLEXIBLE ANTENNAS FOR WEARABLE AND IOT DEVICES IN 5G COMMUNICATION (World Conference on Engineering and Technological Sciences, 2026)
The rapid evolution of fifth-generation (5G) wireless communication and the Internet of Things (IoT) has accelerated the development of flexible antenna technologies capable of supporting lightweight, compact, and wearable electronic systems. Unlike conventional rigid antennas, flexible antennas can conform to curved surfaces while maintaining satisfactory electromagnetic performance under mechanical deformation. These characteristics make them suitable for applications in healthcare monitoring, wireless body area networks (WBANs), smart textiles, consumer electronics, industrial IoT, and next-generation communication systems. This paper presents a concise review of recent developments in flexible antenna technology, focusing on substrate materials, conductive elements, antenna design approaches, fabrication techniques, and performance evaluation. Furthermore, major application domains, including wearable healthcare devices, IoT systems, and 5G communication, are discussed together with current technical challenges such as body-loading effects, mechanical reliability, and fabrication complexity. Finally, emerging research directions involving advanced materials, additive manufacturing, artificial intelligence-assisted antenna optimization, and sixth-generation (6G) wireless systems are highlighted. This review provides researchers and engineers with an overview of current progress while identifying opportunities for future development of flexible antenna technologies.
Keywords: Flexible antenna, Wearable antenna, Internet of Things, 5G communication, Flexible electronics, Microstrip antenna.